Using content-based and task-based teaching in a critical thinking setting to improve EFL learners’ writing - Hamid Marashi; Samira Mirghafari (Studies in English Language and Education, 2019)
The purpose of this study was to compare the effect of content-based and task-based instruction in a critical thinking setting on EFL learners’ writing. Accordingly, 60 female learners out of a total number of 90 intermediate learners studying at a language school in Tehran were selected after taking a piloted sample of the Preliminary English Test (PET) for homogenization prior to the study. Subsequently, they were put into two experimental groups: 30 learners in the content-based teaching group and 30 learners undergoing the task-based teaching treatment. Both experimental groups experienced the two teaching approaches in a critical thinking setting. A sample PET writing was administered as the post-test of the study after 16 sessions of treatment spanning nine weeks. A comparison of the mean scores of the two groups on this post-test through an independent samples t-test revealed that there was no significant difference between the two groups at the post-test. The probable reason for this result together with the pedagogical implications of this study and the suggestions for further research are elaborated extensively in the paper.